Exploring content of misinformation about HPV vaccine on twitter. - Kornides, Melanie L.; Badlis, Sarah; Head, Katharine J.; Putt, Mary; Cappella, Joseph; Gonzalez-Hernadez, Graciela (Journal of Behavioral Medicine, 2023)
Although social media can be a source of guidance about HPV vaccination for parents, the information may not always be complete or accurate. We conducted a retrospective content analysis to identify content and frequencies of occurrence of disinformation and misinformation about HPV vaccine posted on Twitter between December 15, 2019, through March 31, 2020, among 3876 unique, English language #HPV Tweets, excluding retweets. We found that 24% of Tweets contained disinformation or misinformation, and the remaining 76% contained support/education. The most prevalent categories of disinformation/misinformation were (1) adverse health effects (59%), (2) mandatory vaccination (19%), and (3) inefficacy of the vaccine (14%). Among the adverse health effects Tweets, non-specific harm/injury (51%) and death (23%) were most frequent. Disinformation/misinformation Tweets vs. supportive Tweets had 5.44 (95% CI 5.33–5.56) times the incidence rate of retweet. In conclusion, almost one-quarter of #HPV Tweets contained disinformation or misinformation about the HPV vaccine and these tweets received higher audience engagement including likes and retweets. Implications for vaccine hesitancy are discussed.